A lágrima de um caeté, de Nísia Floresta, como corpus sensível e possível para o 9º ano - Pereira, Waldemar Valença (2015)
In Brazil and Europe, after knowing the production of literary works, of Dionysia Gonçalves Pinto (1810-1885), better known as Nísia Floresta, which along with various books published, also wrote a epic poem indianista and indigenous, in the nineteenth century, entitled A lágrima de um Caeté (1849). We decided to produce a scientific research, professional perspective, to make better education and learning in Portuguese Language, with one literary text. So we decided to develop studies A lágrima de um Caeté of Nisia Floresta as one sensitive and possible corpus for a education or as way to mediate literary text reading times among young people 13-17 years old. Then our pedagogical action ran a critical way, we base ourselves in scientific research of Anazildo Vasconcelos da Silva and him theory known as Literary Semiotization of Discourse, later developed also by the writer Christina Ramalho, and literary historiography studies of Constance Lima Duarte. Other intellectuals like Tzvetan Todorov, Umberto Eco and Roland Barthes, added to Romero, Marisa Lajolo, Regina Zilberman and Antonio Candido, among others. Our pedagogical and literary project entitled "Poetry ilustrations 2015" to show for classroom that learn about skills and competencies for identify the "epic heroism" in epic poems. We promote a production illustrations, created from stanzas or episodes in A lágrima de um Caeté. We published and illustrated two versions of A lágrima de um Caeté: one e-book, available on our website on the Internet; otherwise it was a printed book for to restore the collections in school library. Therefore, to strengthen our teaching practices to encourage reading, we perform one ludic game: "Ask and you will know". Then, we aim to contribute to a critical review on school debates, especially of equal rights issues, related to culture and your ethnics problems in Brazil.